Copper pyrazole addition regulates soil mineral nitrogen turnover by mediating microbial traits - Wang, Yuming; Zhong, Wenling; Zhang, Xiwen; Cao, Minghui; Ni, Zheng; Zhang, Mengxia; Li, Jiangye; Duan, Yan; Wu, Lifang (Frontiers in Microbiology, 2024)
The huge amount of urea applied has necessitated best-developed practices to slow down the release of nitrogen (N) fertilizer while minimizing nitrate loss. However, the impact of nitrification inhibitors on mineral-N turnover and the associated microbial mechanisms at different stages remains unknown. A 60-day incubation experiment was conducted with four treatments: no fertilizer (CK), urea (U), urea with copper pyrazole (UC), and urea coated with copper pyrazole (SUC), to evaluate the changes about soil ammonia N (NH_4^+-N) and nitrate N (NO_3^–N) levels as well as in soil microbial community throughout the whole incubation period. The results showed that copper pyrazole exhibited significantly higher inhibition rates on urease compared to other metal-pyrazole coordination compounds. The soil NH_4^+-N content peaked on the 10th day and was significantly greater in UC compared to U, while the NO_3^–N content was significantly greater in U compared to UC on the 60th day. Copper pyrazole mainly decreased the expression of nitrifying (AOB-amoA) and denitrifying (nirK) genes, impacting the soil microbial community. Co-occurrence network suggested that Mycobacterium and Cronobacter sakazakii-driven Cluster 4 community potentially affected the nitrification process in the initial phase, converting NH_4^+-N to NO_3^–N. Fusarium-driven Cluster 3 community likely facilitated the denitrification of NO_3^–N and caused N loss to the atmosphere in the late stage. The application of copper pyrazole may influence the process of nitrification and denitrification by regulating soil microbial traits (module community and functional genes). Our research indicates that the addition of copper pyrazole alters the community function driven by keystone taxa, altering mineral-N turnover and supporting the use of nitrification inhibitors in sustainable agriculture.